1989
DOI: 10.1680/geot.1989.39.2.323
|View full text |Cite
|
Sign up to set email alerts
|

Problems with interpretation of sand state from cone penetration test

Abstract: Considerable attention has been given to the inference of sand density from indirect tests, particularly the cone penetration test (CPT). Data from tests performed in large-scale chambers have demonstrated that for a given sand there is an approximately unique relationship between CPT tip resistance, density (or void ratio) and effective stress level. Data have been presented to support the supposition that CPT tip resistance, if normalized by division by the mean effective stress, is uniquely related to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 0 publications
1
14
1
1
Order By: Relevance
“…The Q p -w relation appears to be linear for each level of stresses and this observation supports the dependency of the Q p -w relation on the stress level. The slopes (m) of each relationship are observed to be similar, within the range of 6.9-8.2, which is consistent with the result obtained by Sladen (1989).…”
Section: Evaluation Of State Parameter Of Jeju Sand 43supporting
confidence: 90%
See 2 more Smart Citations
“…The Q p -w relation appears to be linear for each level of stresses and this observation supports the dependency of the Q p -w relation on the stress level. The slopes (m) of each relationship are observed to be similar, within the range of 6.9-8.2, which is consistent with the result obtained by Sladen (1989).…”
Section: Evaluation Of State Parameter Of Jeju Sand 43supporting
confidence: 90%
“…This observation conflicts with Sladen (1989), in which the j value of Ticino sand decreases with an increasing stress level. In other words, the Q p -w relation of Jeju sand moves to the right side in the plot when increasing the stress level.…”
Section: Effect Of Stress Level On Q P -W Relationcontrasting
confidence: 68%
See 1 more Smart Citation
“…Therefore, when using spherical cavity expansion theory to interpret CPT results, the assumed value for G must closely represent the elastic behaviour of the sand. However, the sensitivity of s [13,37]. This dependency is also observed when crushing is included, as shown in Figure 7, where a series of results were generated for different values of p 0 0 in which G/G max was held constant.…”
Section: Resultsmentioning
confidence: 71%
“…Collins et al (1992) provided the first realistic model for cavity expansion in soil using a state parameter based numerical analysis. Their results showed that the relation between normalised CPT tip resistance and ł 0 was still affected by the stress level (as suggested by Sladen, 1989) and depended on material properties of the sand. Shuttle & Jefferies (1998) used a general work hardening/softening critical state model to evaluate changes in CPT calibration in terms of critical state properties M, º that can be determined in routine triaxial testing of reconstituted samples.…”
Section: Introductionmentioning
confidence: 90%